INTERVENSI SISTEMIK PENCEGAHAN DAN PEMBERANTASAN PENYALAHGUNAAN DAN PEREDARAN GELAP NARKOBA (P4GN) BERBASIS KOMUNITAS DI PROVINSI BANTEN - Wicaksana, Harits Hijrah; Munandar, Teguh Aris (Jurnal Administrasi Publik, 2024)
Drug misuse is a complicated issue that contributes to several social and health issues. The National Narcotics Agency (BNN) had previously used various strategies to prevent drug abuse, including outreach, public awareness campaigns, informational media campaigns, and other prevention activities that helped the central and regional levels of prevention targets to be met. In actuality, though, it's believed that the current strategy falls short in terms of lowering the prevalence of drug misuse. A specific action taken by communities of interventionists in an attempt to effect change or develop a tool for reasoned issue resolution is known as the community-based systemic intervention paradigm. The intervention procedure aims to affect the target or social environment in a way that will help the person's capacity to perform social functions return or even improve. A qualitative methodology is used in the research process. A comprehensive intervention strategy for social communitybased prevention, eradication, abuse, and illegal drug trafficking is also the outcome of this research. "By and for the community" is how community collaboration to prevent drug misuse is implemented.